Neuroprotective Effects of Polydeoxyribonucleotide in a Murine Model of Cadmium Toxicity. (29th August 2018) - Marini, Herbert R.; Puzzolo, Domenico; Micali, Antonio; Adamo, Elena Bianca; Irrera, Natasha; Pisani, Antonina; Pallio, Giovanni; Trichilo, Vincenzo; Malta, Consuelo; Bitto, Alessandra; Squadrito, Francesco; Altavilla, Domenica; et al.
Abstract : Cadmium (Cd) is a harmful heavy metal, which causes severe brain damage and neurotoxic effects. Polydeoxyribonucleotide (PDRN) stimulates adenosine A2A receptor, thus contrasting several deleterious mechanisms in course of tissue damages. We aimed to investigate the possible neuroprotective effect of PDRN in a murine model of Cd-induced brain toxicity. Male C57 BL/6J mice were treated as follows: vehicle (0.9% NaCl, 1 ml/kg/day), PDRN (8 mg/kg/day), CdCl2 (2 mg/kg/day), and CdCl2  + PDRN. Animals were tested with the Morris water maze test to assess spatial memory and learning. After 14 days of treatment, brains were processed to evaluate the presence of edema in the cerebral tissue, the expression of mammalian target of rapamycin kinase (mTOR) and brain-derived neurotrophic factor (BDNF), and the morphological behavior of the hippocampal structures. After CdCl2 administration, the escape latency was high, protein expression of BDNF was significantly decreased if compared to controls, mTOR levels were higher than normal controls, and brain edema and neuronal damages were evident. The coadministration of CdCl2 and PDRN significantly diminished the escape latency, increased BDNF levels, and decreased protein expression of mTOR. Furthermore, brain edema was reduced and the structural organization and the number of neurons, particularly in the CA1 and CA3 hippocampal areas, were improved. In conclusion, a functional, biochemical, and morphological protective effect of PDRN against Cd induced toxicity was demonstrated in mouse brain.